2008
DOI: 10.1213/ane.0b013e318174df8b
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypoxemia in Morbidly Obese Patients With and Without Obstructive Sleep Apnea Undergoing Laparoscopic Bariatric Surgery

Abstract: In morbidly obese subjects, in the first 24 h after laparoscopic bariatric surgery, OSA does not seem to increase the risk of postoperative hypoxemia. Our data confirm that morbidly obese subjects, with or without OSA, experience frequent oxygen desaturation episodes postoperatively, despite supplemental oxygen therapy suggesting that perioperative management strategies in morbidly obese patients undergoing laparoscopic bariatric surgery should include measures to prevent postoperative hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(113 citation statements)
references
References 32 publications
8
99
0
6
Order By: Relevance
“…[25][26][27][28][29][30][31] Only a few studies have evaluated postoperative complications in patients who underwent other types of surgery. 22,[32][33][34][35][36] Our study complements this growing body of literature by demonstrating that OSA patients undergoing different types of surgery have an increased rate of postoperative complications, mainly oxygen desaturation. In a retrospective study of 101 patients with OSA who were undergoing hip replacement or knee replacement, Gupta et al 22 demonstrated that patients with OSA have an increased incidence of total postoperative complications and major complications.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…[25][26][27][28][29][30][31] Only a few studies have evaluated postoperative complications in patients who underwent other types of surgery. 22,[32][33][34][35][36] Our study complements this growing body of literature by demonstrating that OSA patients undergoing different types of surgery have an increased rate of postoperative complications, mainly oxygen desaturation. In a retrospective study of 101 patients with OSA who were undergoing hip replacement or knee replacement, Gupta et al 22 demonstrated that patients with OSA have an increased incidence of total postoperative complications and major complications.…”
Section: Discussionsupporting
confidence: 64%
“…22,34,35 However, a recent study of 31 OSA and 9 non-OSA morbidly obese patients did not find a difference in the number of hypoxemic episodes during the first 24 hr after surgery. 36 This similarity of observed events may have been due to the high percentage of patients in both groups receiving oxygen therapy during the first 24 hr after surgery. 36 Recently, we found that the apnea-hypopnea index (AHI) and the oxygen-desaturation index are greater among OSA patients on the third postoperative night compared with either the first postoperative night or preoperatively.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…4 Morbidly obese patients, with or without OSA, have been shown to experience frequent episodes of oxygen desaturation following laparoscopic bariatric surgery, despite supplemental oxygen therapy. 5 Alterations in respiratory physiology include increased oxygen consumption, higher respiratory rates, reduced lung volumes (most notably functional residual capacity), significantly higher minute ventilation, reduced total respiratory system compliance, and increased airway resistance (Table). 6 The association of obesity with widening of the alveolararterial O 2 gradient appears to be due to ventilation-perfusion mismatch caused by microatelectasis, particularly when the patient is in the supine position.…”
Section: Airway Patency and Respiratory Physiology In Obese Patientsmentioning
confidence: 99%
“…Direct laryngoscopic view may be affected by patient positioning and can be optimized by aligning the external auditory meatus with the sternal notch, as discussed later in the review. 23 Overall lack of agreement on whether tracheal intubation is more difficult in the morbidly obese may be due to particular confounders, including variations in the definitions of difficult intubation (more than three attempts, intubation difficulty scale [ 5) and difficult laryngoscopy (Cormack and Lehane grade C 3), patient position, operator experience, and laryngoscopy technique (direct vs video laryngoscopy). There is agreement, however, that a combination of features, such as Mallampati score C 3 and larger neck circumference, in the obese patient does increase the risk of difficult laryngoscopy and difficult tracheal intubation.…”
Section: Direct Laryngoscopy and Intubationmentioning
confidence: 99%